Citra Tokoh Kepemimpinan Politik Ratu Tatu Chasanah dalam Perspektif Teori Feminisme Eksistensial - Muhammad Daffa Pratama; Muhammad Adjie Akbar; Ika Arinia Indriyany (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the political leadership image of Ratu Tatu Chasanah through the perspective of Simone de Beauvoir’s existentialist feminism within the context of local politics in Indonesia. The research employed an empirical qualitative approach using a descriptive case study design focused on the political dynamics of Serang Regency. Data were collected through semi structured interviews, documentation studies, media reports, government archives, and academic literature related to women’s leadership and feminist political discourse. The findings demonstrate that Ratu Tatu Chasanah’s leadership represents a form of women’s existential affirmation within a patriarchal political structure through active participation in governance, strategic decision making, and the construction of public legitimacy. Her leadership also contributed to the transformation of social perceptions regarding women’s political capacities and weakened gender based stereotypes in local governance. From the perspective of existentialist feminism, political leadership becomes a medium through which women negotiate subjectivity, autonomy, and social recognition within contemporary democratic institutions.